Efektivitas Media Padlet dalam Meningkatkan Keterampilan Menulis Teks Biografi Siswa: The Effectiveness of Padlet Media in Improving Students' Biographical Text Writing Skills - Sianipar, Desi Sagita Ronauli; Gusar, Martua Reynhat Sitanggang; Simanjuntak, Harlen (Information Technology and Science(ITScience), 2025)
This study aims to analyze the effectiveness of using Padlet media in enhancing the biographical writing skills of Grade X students at SMA Negeri 7 Medan during the 2024/2025 academic year. The initial problem identified was the low level of students' writing skills, particularly in aspects such as idea organization, biographical plot arrangement, language use, and spelling accuracy. Of the 36 students who became the research sample, selected through a simple random sampling technique, 80% obtained scores below the Minimum Completion Criteria (KKM). This study employed a one-group pretest–posttest design, where students received a pretest and a posttest after implementing Padlet as a learning medium. The assessment instrument covered five main aspects, namely orientation, problem events, reorientation, language use, and writing style. The results showed a significant improvement in all aspects of writing skills. The students' average score increased from 57.58 in the pretest to 75.05 in the posttest. The results of the paired t-test show that t_count = 9.8184 is greater than t_table = 1.66691 at a significance level of 0.05, so the Alternative Hypothesis (Ha) is accepted. These findings suggest that Padlet effectively enhances students' writing skills through its collaborative features, visual workspaces, and easy feedback, allowing students to compose and revise texts in a more structured manner. Thus, this study confirms that Padlet is a relevant and efficient digital media to support learning to write biographical texts. Further research is recommended to employ an experimental design with a control group and a larger sample size.